Growth differentiation factor 15 in anaemia of chronic disease, iron deficiency anaemia and mixed type anaemia - Theurl, Igor; Finkenstedt, Armin; Schroll, Andrea; Nairz, Manfred; Sonnweber, Thomas; Bellmann‐Weiler, Rosa; Theurl, Milan; Seifert, Markus; Wroblewski, Victor J.; Murphy, Anthony T.; Witcher, Derrick; Zoller, Heinz; et al. (British journal of haematology, 2010)
Summary Recently, the iron and erythropoiesis‐controlled growth differentiation factor 15 (GDF15) has been shown to inhibit the expression of hepcidin in β‐thalassaemia patients, thereby increasing iron absorption despite iron overload. To access the diagnostic and pathogenic impact of GDF15 in inflammatory anaemia the association of GDF15 expression with serum iron parameters and hepcidin was studied in patients suffering from iron deficiency anaemia (IDA), anaemia of chronic disease (ACD) and ACD subjects with true iron deficiency (ACD/IDA). GDF15 was significantly increased in both ACD and ACD/IDA, but not in IDA subjects as compared to controls. In contrast, hepcidin levels were significantly lower in IDA and ACD/IDA subjects than in ACD patients. IDA and ACD/IDA, but not ACD, showed an association between GDF15 and soluble transferrin receptor, an indicator of iron requirement for erythropoiesis. However, GDF15 did not correlate to hepcidin in either patient group. While GDF15 levels were linked to the needs for erythropoiesis and iron homeostasis in IDA, the immunity‐driven increase of GDF15 may not primarily affect iron homeostasis and hepcidin expression. This indicates that other ACD‐related factors may overcome the regulatory effects of GDF15 on hepcidin expression during inflammation.